Wydrukowanie tekstu - wydrukowanie literatury. O konsekwencjach tekstualizacji przekazów oralnych - Karpowicz, Agnieszka (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
The article concerns the impact of language textualization processes on the origin of literary and artistic categories. I argue that the creation of typographic, visual forms of works which previously functioned rather as performances is one of the basic practices of print culture. By analyzing selected Polish works, which are treated as „literary monuments”, I demonstrate the role and significance of these visual transformations.
Keywords: oralność; literatura staropolska; tekstualizacja